Biological monitoring water quality of Zagyva river by means of zooplankton - Tajthy, Dóra; Bayoumi Hamuda, Hosam E.A.F.; Zsuga, Katalin; Pekli, József (JOURNAL OF LANDSCAPE ECOLOGY, 2009)
Water is affected by several diffuse and pointwise of contamination sources, which causes variation in water quality. The observation of the biological components in an aquatic ecosystem is one of the best applied method to follow such changes, because the biological components often regenerate slower than the contaminated material in the water. The present study gives a general review about the presence of zooplankton during the spring and the summer periods of the Zagyva River This tendency can help us to draw a conclusion from the ecological state point of view. 82 species were detected, including 68 of Rotatoria, 10 of Cladocera and 4 of Copepoda. Our survey suggests that the zooplankton population in water bodies is diverse. The results indicated that the presence of Eurytemora velox zooplankton rose up the natural value of the area such as at the sampling place of Újszász. The trophity, the saprobity, the seasonal variation and the annual changing of water level influenced the composition of zooplankton communities. At Nagybátony located in the upper region of the River, there were a very high number of zooplankton communities with a small numerical value of diversity (2.51 in spring and 2.91 in summer) as compared with the other investigated locations. At Jásztelek location in the lower region of the River, the summer invesigation showed that there is a small number of zooplankton population communities according to the width body of the River at that this location with small numerical values of diversity (2.81 in summer). The results indicated that the population of zooplankton in the River was low at the upper region and high at the lower region, and this should be in opposite form according to the ecological roles in aquatic environments. This observation and the noted, low diversity may be occurred because of an unfavourable ecological state. This indicated that the local contamination or the transported pollution of the watercourses which flow into the Zagyva River could change the communities and other biological content in the investigated sampling points. Finally, determining the presence and abundance of specific groups of zooplankton can provide useful insight into water ecosystem functions. For farther task, physical and chemical investigation of the water body will help us to identify the ecological factors which cause the variation in the zooplankton population.
Keywords: Zagyva River; zooplankton; water ecosystem